THE EFFECT OF ADVANCED GLYCATION END PRODUCT OF HUMAN UMBILICAL CORD MESENCHYMAL STEM CELLS ON VASCULAR ENDOTHELIAL GROWTH FACTOR - Agustono, Bambang; Mundiratri, Karina; Kurdi, Abil; Kuntjoro, Mefina; Hendrijantini, Nike (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the effect of advanced glycation end product- bovine serum albumin medium of human umbilical cord mesenchymal stem cells on vascular endothelial growth factor secretion. Methodology: This was an experimental study with post-test only control group design. Mesenchymal stem cells, isolated from a human umbilical cord were cultured and expanded up to passage 5. The subject groups were divided into a treatment group (aMEM+AGE-BSA medium) and a control group. Flowcytometry assessment was conducted in passage 4 by tripination and suspension of human umbilical cord mesenchymal stem cells in minimum essential medium. Samples collected on days 3, 6, 9, 12, 14, 17 and 21 were subsequently examined with enzyme-linked immunosorbent assay to observe the amount of vascular endothelial growth factor secretion. Results: In the advanced glycation end product- bovine serum albumin group, the peak level of vascular endothelial growth factor secretion occurred on day 3 and gradually declined on day 21, whereas in the control group the peak level reached on day 6 and continued to decrease up to day 21. Conclusion: This research indicated that advanced glycation end product- bovine serum albumin enhances vascular endothelial growth factor secretion by mesenchymal stem cells with maximum secretion occurring on day 3.